A new species of the genus Ceracris Walker, 1870 from Hainan of China (Orthoptera: Acridoidea, Arcypteridae) - Feng, Li; Qiao, Ning; Yin, Hong (Zootaxa, 2018)
The genus Ceracris Walker, 1870 is a median genus in Arcypteridae, which contains 23 species in the world, among them 10 species distributed in China [Walker, 1870; Bolivar, 1914; Uvarov, 1931; Zheng, 1977; Liu, 1981; Zheng, 1983; Yin, 1984; Liang, 1988; Wang, 1992; Liu et Li, 1995; Ou et al, 1995; Yin et al, 1996; Zheng et Xia, 1998; Zhang et al, 2017; Cigliano, 2018]. A new species of the genus i.e. Ceracris jianfenglingensis sp. nov. is described from Hainan, China in this paper. The new species is similar to Ceracris n. nigrocornis Walker, 1870, but differs from latter by antennae wider, length of middle segment 3.4 times of its width; lateral carinae of pronotum almost parallel; length of interspace 1.2 times minimum width in mesosternum of male; cubital area of tegmen without intercalary vein in male; epiphallus with straight bridge and tegmen of female shorter, reaching the end of hind femur only. Type specimens are deposited in the Natural Museum of Hebei University, Baoding, Hebei, China.